Sociology and Anthropology in the People's Republic of China: Report of a Delegation Visit, February-March 1984 (The National Academies Press, 1985)
Keywords: Behavioral and Social Sciences

Report on the Case of Dr. Saad Eddin Mohamed Ibrahim, Imprisoned Sociologist, Cairo, Egypt (The National Academies Press, 2001)
In February 2001 Committee on Human Rights (CHR) member Morton Panish (a member of the NAS and NAE) and former National Academies staff officer Jay Davenport attended the February 2001 hearings in Cairo of the trial of renowned sociology professor, Saad Eddin Ibrahim. This report provides a summary of the February trial cycle and developments in Dr. Ibrahim's case from the time of his arrest in June 2000 through the end of May 2001, when he and 27 staff members of the Ibn Khaldun Center for Development Studies (which he directs) were convicted. It also describes the CHR's efforts in behalf of Professor Ibrahim and provides an overview of the political and legal environment in Egypt at the time. The report concludes that the outlook for the development of a healthy civil society in Egypt appears to be growing dimmer. By prosecuting a person as highly esteemed as Dr. Ibrahim and closing the Ibn Khaldun Center , the government was sending a clear message that there will be little tolerance of those working in Egypt to promote democracy and the growth of civil society there.
Keywords: Behavioral and Social Sciences

In the Light of Evolution: Volume X: Comparative Phylogeography - National Academy of Sciences (The National Academies Press, 2017)
Biodiversity--the genetic variety of life--is an exuberant product of the evolutionary past, a vast human-supportive resource (aesthetic, intellectual, and material) of the present, and a rich legacy to cherish and preserve for the future. Two urgent challenges, and opportunities, for 21st-century science are to gain deeper insights into the evolutionary processes that foster biotic diversity, and to translate that understanding into workable solutions for the regional and global crises that biodiversity currently faces. A grasp of evolutionary principles and processes is important in other societal arenas as well, such as education, medicine, sociology, and other applied fields including agriculture, pharmacology, and biotechnology. The ramifications of evolutionary thought also extend into learned realms traditionally reserved for philosophy and religion. The central goal of the In the Light of Evolution (ILE) series is to promote the evolutionary sciences through state-of-the-art colloquia--in the series of Arthur M. Sackler colloquia sponsored by the National Academy of Sciences--and their published proceedings. Each installment explores evolutionary perspectives on a particular biological topic that is scientifically intriguing but also has special relevance to contemporary societal issues or challenges. This tenth and final edition of the In the Light of Evolution series focuses on recent developments in phylogeographic research and their relevance to past accomplishments and future research directions.
Keywords: Biology and Life Sciences

People Person: The Story of Sociologist Marta Tienda - Diane O'Connell (The National Academies Press, 2006)
Marta Tienda sees life stories in numbers. She is a sociologist, a scientist who studies human society. Numbers are the tools she uses to uncover fascinating information about people and their behavior. As the daughter of an illegal Mexican immigrant, Marta Tienda understands the pain of growing up poor. When her family had to pick crops to earn money, Marta saw firsthand the tough conditions that migrant workers had to endure. It was an experience she would never forget. Marta vowed to use her creativity, strong spirit, and positive attitude to empower those who are less fortunate. Today Marta's expertise is helping government leaders create equal opportunities for millions of people, using numbers to understand why some people have more than others, like a better job, a college education, or a nicer house. People Person is the fascinating story of a Mexican American girl raised in a home without books who grew up to become one of the world's leading sociologists. Marta Tienda's life story bursts with bravery and determination— it will surely affect readers of all ages. This title aligns to Common Core standards: Interest Level Grades 6 - 8; Reading Level Grade level Equivalent: 7.1: Lexile Measure: 1080L; DRA: Not Available; Guided Reading: Z
Keywords: Explore Science

We're Friends, Right?: Inside Kids' Culture - William A. Corsaro (The National Academies Press, 2003)
Sociologists often study exotic cultures by immersing themselves in an environment until they become accepted as insiders. In this fascinating account by acclaimed researcher William A. Corsaro, a scientist "goes native" to study the secret world of children. Here, for the first time, are the children themselves, heard through an expert who knows that the only way to truly understand them is by becoming a member of their community. That's just what Corsaro did when he traded in his adult perspective for a seat in the sandbox alongside groups of preschoolers. Corsaro's journey of discovery is as fascinating as it is revealing. Living among and gaining the acceptance of children, he gradually comes to understand that a child's world is far more complex than anyone ever suspected. He documents a special culture, unique unto itself, in which children create their own social structures and exert their own influences. At a time when many parents fear that they don't spend enough time with their children, and experts debate the best path to healthy development, seeing childhood through the eyes of a child offers parents and caregivers fresh and compelling insights. Corsaro calls upon all adults to appreciate, embrace, and savor their children's culture. He asks us to take a cue from those we hold so precious and understand that "we're all friends, right?"
Keywords: Explore Science; Behavioral and Social Sciences; Education

In the Light of Evolution: Volume V: Cooperation and Conflict - National Academy of Sciences (The National Academies Press, 2011)
Biodiversity--the genetic variety of life--is an exuberant product of the evolutionary past, a vast human-supportive resource (aesthetic, intellectual, and material) of the present, and a rich legacy to cherish and preserve for the future. Two urgent challenges, and opportunities, for 21st-century science are to gain deeper insights into the evolutionary processes that foster biotic diversity, and to translate that understanding into workable solutions for the regional and global crises that biodiversity currently faces. A grasp of evolutionary principles and processes is important in other societal arenas as well, such as education, medicine, sociology, and other applied fields including agriculture, pharmacology, and biotechnology. The ramifications of evolutionary thought also extend into learned realms traditionally reserved for philosophy and religion. The central goal of the In the Light of Evolution (ILE) series is to promote the evolutionary sciences through state-of-the-art colloquia--in the series of Arthur M. Sackler colloquia sponsored by the National Academy of Sciences--and their published proceedings. Each installment explores evolutionary perspectives on a particular biological topic that is scientifically intriguing but also has special relevance to contemporary societal issues or challenges. This book is the outgrowth of the Arthur M. Sackler Colloquium "Cooperation and Conflict," which was sponsored by the National Academy of Sciences on January 7-8, 2011, at the Academy's Arnold and Mabel Beckman Center in Irvine, California. It is the fifth in a series of colloquia under the general title "In the Light of Evolution." The current volume explores recent developments in the study of cooperation and conflict, ranging from the level of the gene to societies and symbioses. Humans can be vicious, but paradoxically we are also among nature's great cooperators. Even our great conflicts-wars-are extremely cooperative endeavors on each side. Some of this cooperation is best understood culturally, but we are also products of evolution, with bodies, brains, and behaviors molded by natural selection. How cooperation evolves has been one of the big questions in evolutionary biology, and how it pays or does not pay is a great intellectual puzzle. The puzzle of cooperation was the dominant theme of research in the early years of Darwin's research, whereas recent work has emphasized its importance and ubiquity. Far from being a rare trait shown by social insects and a few others, cooperation is both widespread taxonomically and essential to life. The depth of research on cooperation and conflict has increased greatly, most notably in the direction of small organisms. Although most of In the Light of Evolution V: Cooperation and Conflict is about the new topics that are being treated as part of social evolution, such as genes, microbes, and medicine, the old fundamental subjects still matter and remain the object of vigorous research. The first four chapters revisit some of these standard arenas, including social insects, cooperatively breeding birds, mutualisms, and how to model social evolution.
Keywords: Biology and Life Sciences

Deadly Lessons: Understanding Lethal School Violence - National Research Council (The National Academies Press, 2003)
The shooting at Columbine High School riveted national attention on violence in the nation's schools. This dramatic example signaled an implicit and growing fear that these events would continue to occur—and even escalate in scale and severity. How do we make sense of the tragedy of a school shooting or even draw objective conclusions from these incidents? Deadly Lessons is the outcome of the National Research Council's unique effort to glean lessons from six case studies of lethal student violence. These are powerful stories of parents and teachers and troubled youths, presenting the tragic complexity of the young shooter's social and personal circumstances in rich detail. The cases point to possible causes of violence and suggest where interventions may be most effective. Readers will come away with a better understanding of the potential threat, how violence might be prevented, and how healing might be promoted in affected communities. For each case study, Deadly Lessons relates events leading up to the violence, provides quotes from personal interviews about the incident, and explores the impact on the community. The case studies center on: Two separate incidents in East New York in which three students were killed and a teacher was seriously wounded. A shooting on the south side of Chicago in which one youth was killed and two wounded. A shooting into a prayer group at a Kentucky high school in which three students were killed. The killing of four students and a teacher and the wounding of 10 others at an Arkansas middle school. The shooting of a popular science teacher by a teenager in Edinboro, Pennsylvania. A suspected copycat of Columbine in which six students were wounded in Georgia. For everyone who puzzles over these terrible incidents, Deadly Lessons offers a fresh perspective on the most fundamental of questions: Why?
Keywords: Health and Medicine; Behavioral and Social Sciences

Statistics on U.S. Immigration: An Assessment of Data Needs for Future Research - National Research Council (The National Academies Press, 1996)
The growing importance of immigration in the United States today prompted this examination of the adequacy of U.S. immigration data. This volume summarizes data needs in four areas: immigration trends, assimilation and impacts, labor force issues, and family and social networks. It includes recommendations on additional sources for the data needed for program and research purposes, and new questions and refinements of questions within existing data sources to improve the understanding of immigration and immigrant trends.
Keywords: Behavioral and Social Sciences

Environmentally Significant Consumption: Research Directions - National Research Council (The National Academies Press, 1997)
There has been much polemic about affluence, consumption, and the global environment. For some observers, "consumption" is at the root of global environmental threats: wealthy individuals and societies use far too much of the earth's resource base and should scale back their appetites to preserve the environment for future generations and allow a decent life for the rest of the world. Other observers see affluence as the way to escape environmental threats: economic development increases public pressure for environmental protection and makes capital available for environmentally benign technologies. The arguments are fed by conflicting beliefs, values, hopes, and fears—but surprisingly little scientific analysis. This book demonstrates that the relationship of consumption to the environment needs careful analysis by environmental and social scientists and conveys some of the excitement of treating the issue scientifically. It poses the key empirical questions: Which kinds of consumption are environmentally significant? Which actors are responsible for that consumption? What forces cause or explain environmentally significant consumption? How can it be changed? The book presents studies that open up important issues for empirical study: Are there any signs of saturation in the demand for travel in wealthy countries? What is the relationship between environmental consumption and human well-being? To what extent do people in developing countries emulate American consumption styles? The book also suggests broad strategies that scientists and research sponsors can use to better inform future debates about the environment, development, and consumption.
Keywords: Behavioral and Social Sciences; Energy and Energy Conservation

A Common Destiny: Blacks and American Society - National Research Council (The National Academies Press, 1989)
"[A] collection of scholars [has] released a monumental study called A Common Destiny: Blacks and American Society. It offers detailed evidence of the progress our nation has made in the past 50 years in living up to American ideals. But the study makes clear that our work is far from over." —President Bush, Remarks by the president to the National Urban League Conference The product of a four-year, intensive study by distinguished experts, A Common Destiny presents a clear, readable "big picture" of blacks' position in America. Drawing on historical perspectives and a vast amount of data, the book examines the past 50 years of change and continuity in the status of black Americans. By studying and comparing black and white age cohorts, this volume charts the status of blacks in areas such as education, housing, employment, political participation and family life.
Keywords: Behavioral and Social Sciences

Science and Technology in the Academic Enterprise: Status, Trends, and Issues - Institute of Medicine; National Academy of Sciences; National Academy of Engineering (The National Academies Press, 1989)
The U.S. academic research enterprise is entering a new era characterized by remarkable opportunities and increased strain. This two-part volume integrates the experiential knowledge of group members with quantitative data analyses in order to examine the status of scientific and technological research in academic settings. Part One reviews the status of the current research enterprise, emerging trends affecting it, and issues central to its future. Part Two is an overview of the enterprise and describes long-term trends in financial and human resources. This new book will be useful in stimulating policy discussions—especially among individuals and organizations that fund or perform academic research.
Keywords: Education

Saragosa, Texas, Tornado May 22, 1987: An Evaluation of the Warning System - National Research Council (The National Academies Press, 1991)
The small community of Saragosa, Texas, was devastated by a violent multiple-vortex tornado on Friday, May 22, 1987. Despite the extensive warning dissemination efforts, which are documented in this book, the overall warning system in Saragosa failed to reach most of the residents in time for them to take effective safety measures. The primary purpose of this book is to combine the information provided by the respondents to a postdisaster survey with the facts surrounding the tornado in order to understand and evaluate the severe weather warning procedures used in Reeves County, Texas, where Saragosa is located. The evaluation of this survey is intended to determine ways of adjusting existing warning systems and better prepare the citizens, public officials, and news media in Reeves County, as well as in every city, county, and township where severe weather threatens lives and property.
Keywords: Earth Sciences

Field Guide to Brazil - National Research Council (The National Academies Press, 1960)
This guide to field research in Brazil is one of a series being issued under the auspices of the Committee on International Anthropology, which was established in 1957 by the Division of Anthropology and Psychology of the National Academy of Sciences — National Research Council. The proposal that such field guides be prepared came from a conference of anthropologists held at Columbia University in December, 1956. The Committee has treated the project as an experimental one, recognizing that the audiences to be addressed are rather diverse, e.g., the research worker with a project and area in hand, graduate training seminars, the social scientist wanting to make professional contacts, and that the materials would have to be stated mostly in general terms. The purpose of Field Guide to Brazil is to provide information which the research worker, entering an area for the first time, should have in order to plan his trip get clearances from governments, deal with interested scientific institutions and scholars, comport himself properly in relations with local leaders, and establish generally a favorable working status for himself prior to the point where he applies his professional techniques to the problem in hand.
Keywords: Biology and Life Sciences

People and Pixels: Linking Remote Sensing and Social Science - National Research Council (The National Academies Press, 1998)
Space-based sensors are giving us an ever-closer and more comprehensive look at the earth's surface; they also have the potential to tell us about human activity. This volume examines the possibilities for using remote sensing technology to improve understanding of social processes and human-environment interactions. Examples include deforestation and regrowth in Brazil, population-environment interactions in Thailand, ancient and modern rural development in Guatemala, and urbanization in the United States, as well as early warnings of famine and disease outbreaks. The book also provides information on current sources of remotely sensed data and metadata and discusses what is involved in establishing effective collaborative efforts between scientists working with remote sensing technology and those working on social and environmental issues.
Keywords: Earth Sciences

The Role of Diffusion Processes in Fertility Change in Developing Countries - National Research Council (The National Academies Press, 1999)
This report summarizes presentations and discussions at the Workshop on the Social Processes Underlying Fertility Change in Developing Countries, organized by the Committee on Population of the National Research Council (NRC) in Washington, D.C., January 29-30, 1998. Fourteen papers were presented at the workshop; they represented both theoretical and empirical perspectives and shed new light on the role that diffusion processes may play in fertility transition. These papers served as the basis for the discussion that is summarized in this report.
Keywords: Behavioral and Social Sciences

Fostering Research on the Economic and Social Impacts of Information Technology - National Research Council (The National Academies Press, 1998)
The tremendous growth in use of information technology (IT) has led to an increased interest in understanding its social and economic impacts. This book presents examples of crosscutting research that has been conducted to understand the impact of information technology on personal, community, and business activities. It explores ways in which the use of methodology from economics and social sciences contributes to important advances in understanding these impacts. The book discusses significant research issues and concerns and suggests approaches for fostering increased interdisciplinary research on the impacts of information technology and making the results of this research more accessible to the public and policymakers. This volume is expected to influence funding priorities and levels of support for interdisciplinary research of this kind.
Keywords: Computers and Information Technology

Understanding and Preventing Violence, Volume 3: Social Influences - National Research Council (The National Academies Press, 1994)
This volume examines social influences on violent events and violent behavior, particularly concentrating on how the risks of violent criminal offending and victimization are influenced by communities, social situations, and individuals; the role of spouses and intimates; the differences in violence levels between males and females; and the roles of psychoactive substances in violent events.
Keywords: Behavioral and Social Sciences

Toward an Understanding of Metropolitan America: Report of the Social Science Panel on the Significance of Community in the Metropolitan Environment of the Advisory Committee to the Dept. of Housing and Urban Development, Assembly of Behavioral and Socia - National Research Council (The National Academies Press, 1974)
Keywords: Industry and Labor

Enhancing Organizational Performance - National Research Council (The National Academies Press, 1997)
Total quality management (TQM), reengineering, the workplace of the twenty-first century—the 1990s have brought a sense of urgency to organizations to change or face stagnation and decline, according to Enhancing Organizational Performance. Organizations are adopting popular management techniques, some scientific, some faddish, often without introducing them properly or adequately measuring the outcome. Enhancing Organizational Performance reviews the most popular current approaches to organizational change—total quality management, reengineering, and downsizing—in terms of how they affect organizations and people, how performance improvements can be measured, and what questions remain to be answered by researchers. The committee explores how theory, doctrine, accepted wisdom, and personal experience have all served as sources for organization design. Alternative organization structures such as teams, specialist networks, associations, and virtual organizations are examined. Enhancing Organizational Performance looks at the influence of the organization's norms, values, and beliefs—its culture—on people and their performance, identifying cultural "levers" available to organization leaders. And what is leadership? The committee sorts through a wealth of research to identify behaviors and skills related to leadership effectiveness. The volume examines techniques for developing these skills and suggests new competencies that will become required with globalization and other trends. Mergers, networks, alliances, coalitions—organizations are increasingly turning to new intra- and inter-organizational structures. Enhancing Organizational Performance discusses how organizations cooperate to maximize outcomes. The committee explores the changing missions of the U.S. Army as a case study that has relevance to any organization. Noting that a musical greeting card contains more computing power than existed in the entire world before 1950, the committee addresses the impact of new technologies on performance. With examples, insights, and practical criteria, Enhancing Organizational Performance clarifies the nature of organizations and the prospects for performance improvement. This book will be important to corporate leaders, executives, and managers; faculty and students in organizational performance and the social sciences; business journalists; researchers; and interested individuals.
Keywords: Industry and Labor; Behavioral and Social Sciences

The New Year's Eve Flood on Oahu, Hawaii: December 31, 1987 - January 1, 1988 - National Research Council (The National Academies Press, 1991)
The flood that greeted the new year in 1988 brought home the uncomfortable realization that many suburban areas of eastern Oahu are at risk from sudden and, in some cases, unpredictable flooding. Torrential rains fell over the southeastern portion of the island on New Year's Eve, precipitating major flooding in several suburban neighborhoods and resulting in $34 million in damages. Neither the current meteorological capabilities nor the present flood control structures for the Oahu area proved adequate to predict or control the deluge. This book documents and analyzes the meteorological conditions leading to the torrential rains, the causes and patterns of flooding, the performance of flood control structures in affected areas, the extent of damages, and the effectiveness of the local emergency response and recovery actions. Conclusions and recommendations are drawn from the analyses.
Keywords: Earth Sciences